Collecting and compiling: The activity of seeking pictures in primary school - Lundh, Anna Hampson; Alexandersson, M. (Emerald Group Publishing Limited, 2012)
Purpose: The aim of this study is to further understanding of the situated activity of seeking pictures. It relates to an ongoing discussion on how multimodal information literacies are enacted in different social practices. Design/methodology/approach: In order to understand the characteristics of the communication and interactions in the activity of seeking pictures, video recordings from an ethnographic study of primary school children working with problem-centred assignments have been analysed. Findings: The analysis reveals how the activity of seeking pictures is shaped by the assumption that pictures are different from facts and information; pictures are seen primarily as having decorative functions. The activity is also characterised by playful, yet efficient cooperation between the children; they make the activity meaningful by transforming it into a play and game activity where pictures become important as physical objects, but not as a semiotic means of learning. Research limitations/implications: The study is limited to the activity of seeking pictures in a specific primary school; however, it shows how modes other than textual modes can be included in the study of information activities. Practical implications: The study reveals the need for developing methods for enhancing children's possibilities to critically examine and learn from visual material, such as pictures. Originality/value: Research on information seeking and information literacies rarely focus on multimodal aspects of information activities or the seeking of pictures outside special collections, despite the increased significance of visual material in the contemporary media landscape. This paper shows how studies of multimodal information activities can be designed.